STUDY OF THE ANTIOXIDANT ACTIVITY OF ESSENTIAL OILS WHEN MAKING SMOKED SAUSAGE FROM MARAL MEAT - Myshalova O.M. (Техника и технология пищевых производств)
The given paper deals with the research results of studying the antioxidant properties of essential oils of sage and rosemary and their combinations in minced semi-smoked and boiled-smoked sausages. Basing on the data of organoleptic analysis of semi- smoked sausage the choice and the maximum permissible level of essential oils of sage and rosemary, which is now not more than 20 g per 100 kg of meat raw materials, has been established. The additives introduced largely take part in the formation of flavor and aroma; they slightly affect the taste and color of products on the cut. Due to the mixing of sage and rosemary oils a bitter taste and medicinal camphor smell are softened. The accelerated oxidation method is used to compare the efficiency of antioxidant properties of essential oils of sage and rosemary added to fats and oils. Induction oxidation periods of pork fat have been determined depending on the type of essential oils introduced. The maximum inhibitory effect is achieved by the joint usage of sage and rosemary oils. The introduction into oxidation systems of the combination of essential oils of sage and rosemary solved in vegetable oils in concentrations from 0.005 to 0.02% reduces the rate of lipid oxidation regardless of the solvent. Samples of pork fat in the presence of cedar oil and essential oils of sage and rosemary have high concentration of antioxidants possessing the antiradical activity with significant induction period; they have higher stability to oxidation changes when heating in comparison with sunflower oil. It has been proved that essential oils of sage and rosemary enable us to stop oxidation of heme pigments of maral meat and create conditions for restoring metmyoglobin.